THE EFFECTS OF PRICE AND PROMOTION OF DECISION TO PURCHASE BRAND “ACER” LAPTOP - Isyanto, Puji; Sungkono; Haizam Mohd Saudi, Mohd (International Journal of Psychosocial Rehabilitation, 2020)
Laptop is a device that is very important Because it helps every individual the usual offer section to the technology of such students and college students to make it Easier in carrying out almost every task acer always top ranked the top brand in an index on 2016 -2018 year. However in three years the percentage of the acer decline every year though still be ranked first. This is the caused by the increasing number of competitors who give a lower price and promotion that has intensively by a competitor. So as to the make the community a switch to using a competitor’s products. Type of this research is explanatory research, with a population of about 100 respondents who buy and use the brand acer laptop. The sample collection to research it uses a non-probablility sampling. The sample collection technique use purposive sampling. Data collected through the questionnaire. The method of analysis used the data the use of tabulating the cross, correlation, regression, simple regression, and multiple regression by using SPSS application. This study concludes that price and promotion influential of the decision the purchase from, whether partial and a stimulant, promotion variables have more impact of variable price. Based on it, acer Researchers suggest that company would have to increase is back promotion that consumers know that acer laptop acer laptop is numer one in Indonesia and reevaluate Also the prices offered them has Appropriate or not